2009 International Conference on New Trends in Information and Service Science 2009
DOI: 10.1109/niss.2009.91
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mobile Self-Efficacy on Attitude towards Mobile Advertising

Abstract: Mobile advertising employs mobile devices such as cell phones and PDAs to transmit advertising information to users. The chief difference between mobile advertising and traditional advertising is that mobile advertising must employ wireless networks and mobile devices; as a consequence, apart from advertisement content, the factors affecting attitude towards mobile advertising may also include consumers' mobile technology use self-efficacy.This study develops and validates a mobile selfefficacy construct asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 30 publications
4
34
0
6
Order By: Relevance
“…1), self-efficacy theory suggests that subjective competency assessments frame individuals' engagement with unfamiliar technological environments (e.g., Murphy, Covover and Owen 1989;Compeau and Higgins 1995;Barbeite and Weis 2004;Bucy and Tao 2007). Indeed, recent research on interactive advertising platforms has identified self-efficacy as an important individual-level factor exerting a substantive, often context-dependent, influence on user evaluation and experience (e.g., Liu and Shrum 2002;Lee and Hsieh 2009). Therein, an emerging, albeit relatively scant, body of research has tentatively suggested that elaboration might be dependent upon domain-relevant self-efficacy levels (e.g., Block and Keller 1998;Lo, Wei, and Su 2013;Wang and Wu 2013).…”
mentioning
confidence: 99%
“…1), self-efficacy theory suggests that subjective competency assessments frame individuals' engagement with unfamiliar technological environments (e.g., Murphy, Covover and Owen 1989;Compeau and Higgins 1995;Barbeite and Weis 2004;Bucy and Tao 2007). Indeed, recent research on interactive advertising platforms has identified self-efficacy as an important individual-level factor exerting a substantive, often context-dependent, influence on user evaluation and experience (e.g., Liu and Shrum 2002;Lee and Hsieh 2009). Therein, an emerging, albeit relatively scant, body of research has tentatively suggested that elaboration might be dependent upon domain-relevant self-efficacy levels (e.g., Block and Keller 1998;Lo, Wei, and Su 2013;Wang and Wu 2013).…”
mentioning
confidence: 99%
“…Impact of self-efficacy toward the attitude was validated by [14]: a validity of system reliability is convergently perceived by the users with self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hal ini berarti bahwa informative memiliki pengaruh positif dan signifikan terhadap consumers' attitude towards advertising. Hasil ini sesuai dengan hasil penelitian sebelumnya oleh Lee, Hsieh, & Huang, (2011).…”
Section: Hasil Dan Pembahasanunclassified